"Jerusalem and Athens" in America: On the Biographical Background of Leo Strauss's Four Eponymous Lectures from 1946, 1950, and 1967, And an Abandoned Book Project from 1956/1957 - Kerber, Hannes (Zeitschrift für neuere Theologiegeschichte, 2022)
Throughout his life, Leo Strauss (1899-1973) employed the expression "Jerusalem and Athens" to refer metaphorically to the two opposing poles of his thinking: biblical faith and ancient philosophy. While Strauss continuously stressed that "Jerusalem" and "Athens" pose a radical alternative, which demands a binary choice, he himself did not present his decision to the public. The following essay examines for the first time four different lectures that Strauss gave in New York City (1946 and 1967), Annapolis (1946), and Chicago (1950) under the title "Jerusalem and Athens." Using not only the new first edition of the 1950 lecture published in this volume - Strauss’s most extensive public treatment of the issue - but also dozens of recently discovered archival sources, I try to illuminate the historical settings in which Strauss spoke about the tension between "Jerusalem" and "Athens." This biographical approach highlights rhetorical strategies adopted by Strauss in his lectures and intends to show different reasons he had to abstain from opting publicly for either "Jerusalem" or "Athens." In the concluding part, I discuss Strauss’s previously unknown but well-advanced (if eventually abandoned) plans to publish a monograph entitled Jerusalem and Athens with the University of Michigan Press in 1956/1957.